Free Space - Cucic, Damir (Croatia : Cucic, Damir, 2001)
During the last war in Croatia, many people were forced to leave their homes. This organised and politically premeditated action, called ‘human displacement’, took place especially in the Western part of Croatia, the territory known as Krajina. People from the Serbian minority were forced to go to Serbia or the Republic of Srpska in Bosnia, and became refugees. At the same time, Croats whose houses had been destroyed by Serbs in other parts of the country started to inhabit the empty homes in Krajina. But can you really be happy in somebody else’s house? Are the people who got houses from the government the lucky ones, or also unfortunate? In a rather experimental documentary, the director focuses on one house that is harassed by a plague of snakes. Using hardly any words, he tries to create the atmosphere of a ‘cursed’ house.
Duration: 00:23:00
Keywords: Documentary films